Development and Evaluation of the Walk for Health Program: A Physical Activity Intervention for Adults with Visual Impairments. (March 2016) - Ackley-Holbrook, Elizabeth; Kang, Minsoo; Morgan, Don W.
Background: Although the pervasive comorbidity documented in adults with visual impairments may be linked to physical inactivity, little is known regarding the extent to which mobility and health status can be improved in this population. The aim of this preliminary study was to develop and implement an adaptive, community-based walking program for adults with visual impairments and to evaluate its impact on daily step activity, cardiovascular health, body composition, and lipid function. Methods: During an 8-week period, 17 adults (age = 47.3 ± 12.3 years) with visual impairments were prompted at biweekly intervals (weeks 1, 3, 5) to increase their daily step activity by 1, 000 steps per day and maintain these gains during weeks 2, 4, and 6. Participants were asked to sustain walking levels achieved by week 6 during the final 2 weeks of the program. Results: Following the walking intervention, participants displayed a 78% increase in daily step activity (p < .01), but no improvements in cardiovascular health, body composition, or lipid function were observed. Conclusion: Daily step activity was improved after completion of the walking program, but markers of health-related fitness remained unchanged. Future studies should be conducted to quantify the volume of physical activity required to improve the health status of persons with visual impairments.